1111 Do Sleep Disorder Symptom Endorsements Differ Between ADHD Subtypes?. (27th May 2020) - Seewald, M; Muench, A; Alio, C; Rosenfield, B; DiTomasso, R; Rostain, A; Ramsay, J; Klingman, K; Perlis, M L
Abstract: Introduction: To date, research on differences in sleep complaints between patients with different subtypes of ADHD has been mixed. On balance, the evidence tends towards ADHD-Combined Presentation (ADHD-C) being associated with more severe sleep and sleep-related daytime complaints than ADHD-Primarily Inattentive (ADHD-I). In order to further assess this issue a surveillance study was undertaken in an active ADHD clinic by adding a comprehensive sleep disorders screener (SDS-CL-25) to the clinical intake procedures. These data were used to ascertain whether the two subtypes differ for any of 13 sleep disorders symptoms. Methods: Subjects (n = 132; 83 male, 49 female, mean age 32.8, age range 18-79), presenting to the clinic for evaluation for ADHD were given the SDS-CL-25. The SDS-CL-25 is a 25-item instrument developed to screen for multiple sleep disorders at one time (problems are endorsed on a Likert-scale; 0 = never and 4 = more than 5x/week). Endorsements greater than 3x/week were counted as positive for the symptom and less than three days per week was considered negative. Percent per group was compared using Chi Square Analyses. Cumulative morbidity means were also analyzed using t-tests. The subtype, ADHD-I (n=71) and ADHD-C (N=61), was established using EMR records. Results: No significant differences between patients with ADHD-I and ADHD-C were detected. Conclusion: The lack of finding in the present analysis may reflect a lack of difference or a failure to detect differences based on the small sample sizes or lack of statistical control for likely confounders (age, sex, illness severity or chronicity, SES status, etc.). Analyses are ongoing. Support: No support was provided for this abstract.